Clinical screening of horses and early warning for West Nile virus. (28th February 2016) - Leblond, A.; Lecollinet, S.
Summary: Clinical presentation of West Nile disease in horses is variable, but ataxia, weakness and muscle fasciculations are often observed, sometimes with abnormal behaviour, teeth grinding and bruxism. Practitioners should be aware that horses are more sensitive to infection than man and serve as sentinels for an early warning of West Nile virus circulation in a given area. This early warning allows the implementation of preventive and control measures such as vaccination of horses and mosquito control.